Risk Factors and Clinical Outcomes of Neonatal Sepsis in Manado Tertiary Referral Hospital: A Single-center Study - Wilar, Rocky; Lestari, Hesti (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Neonatal sepsis remains a major cause of morbidity and mortality among newborn infants, both term and preterm. Even with effective treatment, the outcome is still uncertain, with inflated health-care cost due to prolonged length of stay in the Neonatal Intensive Care Unit. AIM: This study aimed to evaluate risk factors and their association with clinical outcomes of neonatal sepsis in a tertiary referral hospital in Manado, Indonesia. METHODS: This is a single-center retrospective cohort study of 365 neonatal sepsis subjects, conducted between January 2016 and December 2018. Risk factors were divided into two groups: Neonatal-related and maternal-related risk factors. Clinical outcomes analyzed were survival outcome (discharged or death) and hospital length of stay. Logistic regression, Mann–Whitney, and Kruskal–Wallis test were used in statistical analysis. RESULTS: From all risk factors, the highest mortality rate was found in neonates with sclerema (83.1%), and the lowest mortality rate in neonates without tachypnea (11.6%). Further multivariate statistical analysis revealed two risk factors associated with mortality, such as tachypnea (OR 4.94, 95% CI 2.257–10.841; p < 0.001) and sclerema (OR 34.47, 95% CI 15.135‒78.509; p < 0.001). Further analysis also reported several risk factors associated with prolonged length of stay, such as very low birth weight (p < 0.001), premature rupture of the membrane (p = 0.009), preterm gestational age (p < 0.001), and non-hospital delivery location (p = 0.013). CONCLUSION: In neonatal sepsis, the presence of tachypnea and sclerema was significant risk factors for mortality. Meanwhile, premature rupture of the membrane, very low birth weight, preterm gestational age, and non-hospital delivery location were risk factors associated with prolonged length of stay.